PEMBERDAYAAN KADER DALAM PENINGKATAN KAPASITAS PENGETAHUAN ORANG TUA TENTANG POLA ASUH PADA ANAK USIA 6 – 23 BULAN UNTUK PENCEGAHAN STUNTING DI DESA PINGARAN ILIR KABUPATEN BANJAR - ERNA FAUZIAH ERNA; Rutmauli Hutagaol; Evi Risa Mariana; Evy Marlinda; Niken Pratiwi; Muhammad Yazid Rizqullah; Noor Latifah Azlina; Gina Azkia Hidayati; Rahma Ainia; I Gede Andhika Prameswara (UPPM Poltekkes Kemenkes Banjarmasin, 2026)
Based on 2024 data, Banjar Regency has stunting data reaching 24.38%. The Astambul sub-district area is one of the location loci that are the focus of intensive stunting handling through the Stunting Case Audit (AKS) program initiated by the Health Office and the Banjar Regency Stunting Reduction Acceleration Team for more targeted interventions. Data from the Banjar Regency Central Statistics Agency shows that the total area of ​​Pingaran Ilir Village is 13.5 km². It is one of 22 villages in the Astambul Sub-district, Banjar Regency, South Kalimantan Province, with a stunting case of 35.82%. This problem is caused by several factors, including low parental knowledge about good parenting and lack of access to information and quality health services. The purpose of this community service is to empower cadres through appropriate socialization and education for parents while increasing the capacity of parental knowledge about good parenting and empowering cadres in supporting sustainability so that partner problems can be addressed thoroughly to reduce the prevalence of stunting in Pingiran Ilir Village. The results of this community service activity successfully increased the knowledge of Posyandu cadres and parents of toddlers about appropriate parenting patterns to prevent stunting in children aged 6–23 months. Pre-post test evaluation showed a significant increase in cadre knowledge from an average score of 85 to 99 and parents from 78 to 93. Empowered cadres were able to deliver continuous education to parents, contributing to changes in better parenting patterns.